THE IMPACT OF FINANCIAL TECHNOLOGY ON SAVING BEHAVIOR OF STUDENTS IN SURABAYA - Dewanti, Aulia Puja; Permana, Sandi Bagas (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2024)
This research aims to investigate the impact of financial technology (fintech) on the saving behavior of students in Surabaya. The study examines the level of fintech adoption, the relationship between fintech usage and saving behavior, and the factors influencing students' decisions to use fintech for saving. Data were collected from a sample of students using questionnaires, and statistical analyses were conducted using descriptive statistics, reliability tests, Pearson correlation, multiple regression, and independent t-tests. Key findings show that 80% of the students have adopted fintech, with a significant positive correlation between fintech usage and saving behavior. Factors such as ease of use, perceived security, and financial literacy are significant predictors of fintech use for saving. The results suggest that fintech is an effective tool to enhance saving habits among students in Surabaya. However, differences in saving behavior between fintech users and non-users are not substantial, highlighting the need to consider selection bias. This research contributes to the understanding of fintech's role in promoting financial inclusion and improving saving behaviors in emerging markets.